Psychosocial factors as predictors of quality of life in chronic portuguese patients - Vilhena, Estela (BioMed Central, 2014)
BACKGROUND: Chronic illnesses are diseases of long duration and generally of slow progression. They cause significant quality of life impairment. The aim of this study was to analyse psychosocial predictors of quality of life and of subjective well-being in chronic Portuguese patients. METHODS: Chronic disease patients (n = 774) were recruited from central Portuguese Hospitals. Participants completed self-reported questionnaires assessing socio-demographic, clinical, psychosocial and outcome variables: quality of life (HRQL) and subjective well-being (SWB). MANCOVA analyses were used to test psychosocial factors as determinants of HRQL and SWB. RESULTS: After controlling for socio-demographic and clinical variables, results showed that dispositional optimism, positive affect, spirituality, social support and treatment adherence are significant predictors of HRQL and SWB. Similar predictors of quality of life, such as positive affect, treatment adherence and spirituality, were found for subgroups of disease classified by medical condition. CONCLUSIONS: The work identifies psychosocial factors associated with quality of life. The predictors for the entire group of different chronic diseases are similar to the ones found in different chronic disease subgroups: positive affect, social support, treatment adherence and spirituality. Patients with more positive affect, additional social support, an adequate treatment adherence and a feel-good spirituality, felt better with the disease conditions and consequently had a better quality of life. This study contributes to understanding and improving the processes associated with quality of life, which is relevant for health care providers and chronic diseases support.